Demystifying the Indigenous College Students’ Learning of English as Determined by Their Language Learning Motivation: A Convergent Parallel Approach - Permangil, Jayson F. (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
The study aimed to assess the motivation and proficiency of English language learning among indigenous college students at Kapalong College of Agriculture, Sciences and Technology in the Municipality of Kapalong, Davao del Norte. It employed a mixed-method approach using a convergent parallel design. The quantitative phase involved 202 students selected through complete enumeration, while the qualitative phase included 17 participants. Standardized questionnaires were used for the quantitative phase, and researcher-made questionnaires were utilized for the qualitative phase. The findings revealed a high level of motivation for language learning and proficiency in English among the respondents. Furthermore, the study found that language learning motivation significantly influences the English proficiency of indigenous college students. The qualitative analysis identified six themes related to the respondents' experiences in learning English, including enhancing communicative competence, various strategies, challenges encountered, intrinsic and extrinsic motivation, and barriers to learning English. Additionally, five themes emerged from participants' insights on the impact of English language learning motivation on their English proficiency, including external factors, benefits of motivation, aspirations, obstacles to growth and development, and facilitation of growth and development. Integrating quantitative and qualitative data resulted in a convergence of variables and phenomena describing students' English language learning experiences.